Substance use in individuals at clinical high risk of psychosis. Issue 11 (August 2015) - Buchy, L.; Cadenhead, K. S.; Cannon, T. D.; Cornblatt, B. A.; McGlashan, T. H.; Perkins, D. O.; Seidman, L. J.; Tsuang, M. T.; Walker, E. F.; Woods, S. W.; Heinssen, R.; Bearden, C. E.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background A series of research reports has indicated that the use of substances such as cannabis, alcohol and tobacco are higher in youth at clinical high risk (CHR) of developing psychosis than in controls. Little is known about the longitudinal trajectory of substance use, and findings on the relationship between substance use and later transition to psychosis in CHR individuals are mixed. Method At baseline and 6- and 12-month follow-ups, 735 CHR and 278 control participants completed the Alcohol and Drug Use Scale and a cannabis use questionnaire. The longitudinal trajectory of substance use was evaluated with linear mixed models. Results CHR participants endorsed significantly higher cannabis and tobacco use severity, and lower alcohol use severity, at baseline and over a 1-year period compared with controls. CHR youth had higher lifetime prevalence and frequency of cannabis, and were significantly younger upon first use, and were more likely to use alone and during the day. Baseline substance use did not differentiate participants who later transitioned to psychosis (n = 90) from those who did not transition (n = 272). Controls had lower tobacco use than CHR participants with a prodromal progression clinical outcome and lower cannabis use than those with a psychotic clinical outcome at the 2-year assessment. Conclusions In CHR individuals cannabis and tobacco use is higher than in controls and this pattern persists across 1 year. Evaluation of clinical outcome may provide additional information on the longitudinal impact of substance use that cannot be detected through evaluation of transition/non-transition to psychosis alone.